Direct hydrothermal synthesis of highly ordered Sn-SBA-15 mesoporous materials - Shah, Pallavi; Ramaswamy, Arumugamangalam V.; Ramaswamy, Veda (Chemistry Letters, 2006)
Well-ordered Sn4+-incorporated mesoporous silica SBA-15 samples have been synthesized from tetraethyl orthosilicate (TEOS) and SnCl4 (Si/Sn = 114-15) using nonionic surfactants under a slightly higher pH medium (optimum H2O to HCl molar ratio) and characterized by XRD (an increase in lattice parameter), TEM (no SnO2 species) and UV-vis spectral (absorption at 211 nm) techniques to show that Sn4+ ions are in tetrahedral coordination in Sn-SBA-15.

Doping-induced microstructural, textural and optical properties of In2Ti1-xVxO5+delta semiconductors and their role in the photocatalytic splitting of water - Shah, Pallavi; Bhange, Deu S.; Deshpande, Aparna; Kulkarni, Mukund S.; Gupta, Narendra M. (Materials Chemistry and Physics, 2009)
The physicochemical properties of V-doped indium titanates (In2Ti1-xVxO5-delta, 0.0 <= x <= 0.2) were investigated by using XPS, powder XRD, UV-vis, SEM and luminescence spectroscopy techniques. The Rietveld refinement of XRD data revealed that even though the V-containing samples were isostructural with In2TiO5 (orthorhombic space group Pnma), a systematic x-dependent variation was noticeable in the Ti-O bond lengths in [TiO6] octahedral units, cell parameters and in the value of delta. XPS results confirmed the coexistence of V5+ and V4+ states, leading thereby to an enhancement in oxygen non-stoichiometry in the doped samples. A loading-dependent progressive shift from 400 to 750 nm was also observed in the onset of the absorption edge, indicating a significant narrowing of the band gap. Furthermore, the samples with higher V-content were comprised of the grain clusters having larger size and an irregular shape. The UV-vis. photoluminescence and thermoluminescence studies indicate that the doping-induced lattice defects may give rise to certain closely spaced acceptor/donor energy levels in between the band gap of host matrix. The indium titanates are found to serve as stable photocatalysts for water splitting under visible light, where oxygen was the major reaction product. The role of microstructural and morphological properties in the photocatalytic activity is discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: In2Ti1-xVxO5+delta photocatalysts; Luminescence spectroscopy; Microstructure; Optical properties; Structure-activity relationship; water splitting